THE INFLUENCE OF SUPERIOR ACCREDITATION IMPROVEMENT MANAGEMENT ON THE IMPROVEMENT OF ISLAMIC SCHOOL INSTITUTIONS - Saefrudin Saefrudin; Agus Irfan; Muhammad Subhan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research aims to examine the influence of superior accreditation management on improving Islamic school institutions in Indonesia. Through a systematic literature review (SLR) approach to 40 relevant scientific sources published in 2021-2024, this research analyzes how the implementation of structured accreditation management contributes to improving the quality of governance, human resource competence, learning quality and institutional competitiveness. The results of the study prove that comprehensive accreditation management, including strategic planning, organizing human resources, visionary leadership, continuous quality control, and digitalization of governance significantly encourages overall improvement of Islamic School institutions. The quality culture formed through the accreditation process is the foundation for sustainable institutional transformation. The implications of this research point to the need to integrate accreditation management as the main strategy for developing the capacity of Islamic education institutions in the competitive era.